Canine Distemper Virus in Tigers (Panthera tigris) and Leopards (P. pardus) in Nepal - Jessica Bodgener; Amir Sadaula; Parbat Jung Thapa; Bhijay Kumar Shrestha; Kamal Prasad Gairhe; Suraj Subedi; Kiran Raj Rijal; Purushotam Pandey; Janardan Dev Joshi; Prakriti Kandel; Babu Ram Lamichane; Chiranjibi Prasad Pokheral; et al. (Pathogens, 2023)
From wild dogs (Lycaon pictus) in the Serengeti to tigers (Panthera tigris altaica) in the Russian Far East, canine distemper virus (CDV) has been repeatedly identified as a threat to wild carnivores. Between 2020 and 2022, six Indian leopards (P. pardus fusca) presented to Nepali authorities with fatal neurological disease, consistent with CDV. Here, we report the findings of a serosurvey of wild felids from Nepal. A total of 48 serum samples were tested, comprising 28 Bengal tigers (P. t. tigris) and 20 Indian leopards. Neutralizing antibodies were identified in three tigers and six leopards, equating to seroprevalences of 11% (CI: 2.8–29.3%, n = 28) and 30% (CI: 12.8–54.3%, n = 20), respectively. More than one-third of seropositive animals were symptomatic, and three died within a week of being sampled. The predation of domestic dogs (Canis lupus familiaris) has been posited as a potential route of infection. A comparison of existing diet studies revealed that while leopards in Nepal frequently predate on dogs, tigers do not, potentially supporting this hypothesis. However, further work, including molecular analyses, would be needed to confirm this.